Reproductive outcomes of yearling Nelore (Bos indicus) heifers submitted or not to ovulation induction protocols prior to a timed-AI protocol - Kolling, Giselly Brasileiro (2025)
The present study aimed to evaluate the reproductive outcomes of Nelore heifers (Bos indicus) subjected or not to ovulation induction protocols prior to a timed-AI protocol (TAI) protocol. For this purpose, 683 heifers were randomly assigned to one of two treatments: 0IND (n = 344), no treatment before TAI; or 2IND (n = 339), subjected to two ovulation induction protocols. On Day 42, heifers in the 2IND group received a progesterone device (P4, 0.5 g), which was maintained until Day 35, when 0.5 mg of estradiol cypionate (EC) was administered. On Day 21, heifers in the 2IND group underwent the same protocol, with the addition of 0.53 mg of cloprostenol sodium (PGF), administered concurrently with P4 removal on Day 14. All heifers received the same FTAI protocol, starting on Day 0 with the insertion of a P4 device (0.5 g), administration of 0.5 mg of PGF, and 1.5 mg of estradiol benzoate (EB). On Day 7, 0.5 mg of PGF, 0.5 mg of EC, and 200 IU of equine chorionic gonadotropin (eCG) were administered intramuscularly, concomitantly with P4 removal and tail-chalk application for estrus detection. On Day 9, 8.4 µg of buserelin acetate was administered, and TAI was performed two days later (Day 9, 46 to 50 hours after P4 removal). Reproductive parameters evaluated included the presence of corpus luteum (CL), uterine diameter, estrus expression, pregnancy per AI (P/AI), and pregnancy loss (PL). Statistical analyses were performed using PROC GLIMMIX of SAS 9.4 (a-cP ≤ 0.05; A,B0.05 < P ≤ 0.10). The results showed that a higher proportion of heifers in the 2IND group had a CL at the beginning of the TAI protocol (Day 0: 62.2 vs. 16.6%) and greater estrus expression compared to the 0IND group (75.2 vs. 66.3%), respectively. However, the 0IND group presented higher P/AI at 40 days compared to the 2IND group (41.6 vs. 35.1%), with no difference in P/AI at Day 70 (35.8 vs. 32.7%) or in final pregnancy rate at 130 days (33.7 vs. 32.1%). Total PL was higher in the 0IND group compared to 2IND (18.9% vs. 8.4%). The presence of CL at the beginning of the protocol was associated with greater estrus expression, higher P/AI, and lower PL, regardless of treatment. Similarly, heifers that expressed estrus had higher P/AI, regardless of treatment. The incidence of CL at the beginning of the FTAI protocol and final P/AI at 130 days were higher in older heifers, whereas PL was higher in younger heifers. Heavier heifers showed better reproductive performance, with higher incidence of CL, greater estrus expression, and higher P/AI. In conclusion, although the ovulation induction protocol resulted in a greater presence of CL, larger uterine diameter, and more estrus expression, no improvement in P/AI was observed compared to untreated heifers.